The Effect of Functional Strength Training Using Relative Weights on Some Special Physical Abilities and Achieving 400m running for Men - Mohamed, Ahmed Fadel; Al-Shamaa, Haider Faeq (Journal of Physical Education, 2021)
The research aimed at designing functional strength training using relative weights that develop special abilities and 400m running achievement for men. The researchers used the experimental method on (8) elite 400m runners (over 20 years) divided equally into two groups; experimental and control to conclude that there is a significant development in the level of special abilities for 400m running due to functional strength training with weights. The researchers recommended using this training for developing muscular strength in all sport activities in general and in 400m running in particular. They also recommended making similar studies using a relative weight that are adjustable.